(untitled) (Research, Society and Development, 2023)
Objective: To highlight the main treatments performed for primary hyperhidrosis in children and adolescents up to 19 years of age. Methods: This is an integrative literature review, through articles published in the PubMed and MEDLINE databases that addressed the theme. Results: Hyperhidrosis is a chronic condition in which there is excessive sweat production in some regions of the body, such as armpits, palms, soles and craniofacial areas. Despite being a disease that mostly affects adults, it is in children that the negative effects become potentiated during biopsychosocial development. However, although it is a treatable condition, a large part of the population, especially the pediatric population, does not adhere to therapy due to lack of information about their own disease and existing treatments. Thus, based on the analyzed articles, a good response and few adverse effects were observed in the use of botulinum toxin type A for the initial treatment of pediatric patients. In addition, the use of anticholinergics such as oxybutynin and glycopyrronic torsylate, iontophoresis and video-assisted thoracoscopic sympathectomy stand out as possible treatments for hyperhidrosis in childhood, with good efficacy and improvement in quality of life. Final considerations: There is a scarcity of data on the treatment of pediatric patients with primary hyperhidrosis, with the need for further studies to assess the real indication, risks and benefits of surgical treatment in pediatric patients. Added to this, there are well-indicated non-surgical treatments, with good response and few adverse effects.